Fluorescein Leakage within Recent Subretinal Hemorrhage in Pathologic Myopia: Suggestive of CNV?. (13th August 2018) - Mi, Lan; Zuo, Chengguo; Zhang, Xiongze; Liu, Bing; Peng, Yuting; Wen, Feng
Abstract : Purpose . To determine whether fluorescein leakage within subretinal hemorrhage is definitely suggestive of choroidal neovascularization (CNV) by multimodal imaging including optical coherence tomography angiography (OCTA). Methods . Twenty-five consecutive highly myopic patients (25 eyes) with fluorescein leakage within subretinal hemorrhage detected within 1 month were prospectively included. All patients underwent OCTA and spectral-domain optical coherence tomography (SD-OCT). The OCTA and SD-OCT findings at the site of fluorescein leakage were analyzed. In cases of a doubtful diagnosis, indocyanine green angiography (ICGA) was also performed to differentiate myopic CNV from lacquer crack if necessary; all patients were followed up by SD-OCT and/or OCTA for at least 2 weeks. Results . In terms of the site of fluorescein leakage, OCTA revealed an abnormal vascular network in the outer retina and a choriocapillaris slab in 22 out of 25 eyes (88%), which were confirmed to be CNV. However, no high-flow signal was observed in 3 of 25 eyes (12%). In these 3 cases, SD-OCT showed a focal rupture of the retinal pigment epithelium-Bruch's membrane-choriocapillaris (RPE-BM-CC) complex and a columnar hyperreflective signal of blood originating from defects with a volcanic geyser-like appearance, and no exudative signs were detected. Notably, all ruptures of the RPE-BM-CC complex were located exactly at lacquer crack sites. Moreover, with the absorption of subretinal hemorrhage, ruptures of the RPE-BM-CC complex spontaneously resolved without any intervention. Considering the multimodal imaging appearance and follow-up outcomes, these 3 eyes were eventually diagnosed as simple bleeding associated with lacquer cracks. Conclusions . Dye leakage within recent subretinal hemorrhage on FA could be caused by new-onset lacquer cracks in pathologic myopia. Multimodal imaging including OCTA is helpful to differentiate lacquer cracks from myopic CNV.